Taxonomic revision of the P. chartergoides species-group of the genus Protopolybia Ducke, 1905 (Hymenoptera: Vespidae, Polistinae) - Dos Santos, José N. A. Junior; Silveira, Orlando T.; Carpenter, James M. (Zootaxa, 2020)
A taxonomic revision of the Protopolybia chartergoides species-group was undertaken. Protopolybia isthmensis (Richards) stat. nov. is elevated to the level of species. The male genitalia of P. chartergoides (Gribodo), P. fuscata (Fox), and P. pallidibalteatus (Cameron) are illustrated and described. New collection records and new identification keys are presented for the species groups of Protopolybia, and the species within the P. chartergoides species-group.